Krisis Akulturasi dan Komodifikasi Agama dalam Konflik Adat Rencong Telang Kerinci - Jafar Ahmad; Nuzul Iskandar (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
This article is intended to analyze the role and position of religion in the Rencong Telang customary conflict in Kerinci Regency, Jambi, which has given rise to the dualism of customary institutions. There are two points of concern that will be highlighted in this article. First, religion and customs are facing an acculturation crisis. Second, efforts to commodify religion in winning the contestation. This study uses qualitative data obtained through interviews, observations, and document studies and then analyzed descriptively. The results showed that the Rencong Telang customary conflict took place when the role and position of religion weakened in the social order so that religion was unable to build reconciliation when adat was in conflict. This condition threatens the acculturation of religion and customs of Rencong Telang, which has been created for a long time and is reflected in the philosophy of “adat bersendi syara’, syara’ bersendi kitabullah.” Furthermore, religion in a vacuum is also vulnerable to being used as a commodity to seize influence and win conflicts by one or both parties.